Peran Permainan Tradisional Petak Umpet Terhadap Pembentukan Karakter Mandiri Siswa Sekolah Dasar - Mochammad Ramdan Samadi; Laesti Nurishlah (STAI Al-Mas'udiyah, 2023)
Games have an important role in developing children's character, especially at the elementary school level. One game that is popular among children is hide and seek. This research conducted a qualitative literature study to explore the role of the traditional game of hide and seek in forming the independent character of elementary school students. In-depth analysis was conducted on various sources relevant to this topic, including journal articles, books, and other related documents. The findings show that the game of hide and seek plays an important role in shaping students' independent character by encouraging independence, initiative and self-confidence. Through play experiences, students learn to make independent decisions, overcome challenges, and develop interpersonal skills. The implication of this research is the importance of considering the integration of traditional games into the elementary school curriculum as an effective strategy to support the formation of students' independent character.